BIMBINGAN BAGI ANAK TUNA CAKAP BELAJAR SD GIDEON KALABAHI - Davitzon Ill Olang; Ester Lanlau, Putri Letde, Yessy Mata, Petrus Mau Tellu Dony, Yermia S Wabang (JIP: Jurnal Ilmu Pendidikan, 2025)
Guidance for children with learning disabilities is very important in achieving educational goals. This guidance is different from children in general. This study aims to identify the existence and role of Guidance and Counseling teachers at Gideon Kalabahi Elementary School in supporting students. The research method used is a qualitative case study with a Semi-Structured interview data collection technique. The results of the study show that Gideon Kalabahi Elementary School does not yet have a Guidance and Counseling teacher, but when there is a problem regarding learning difficulties such as not being able to read, all teachers act as Guidance and Counseling teachers. And there is a program (Reading Game) that can help children with learning difficulties such as not being able to read. This finding emphasizes the importance of special attention for children who experience learning difficulties through programs that are implemented as a strategy in providing assistance to children with learning difficulties. So it is important for elementary schools to overcome problems in children. Elementary schools should have Guidance and Counseling teachers with the aim of being able to provide special assistance to children with learning difficulties (Learning disabilities), but in general at Gideon Kalabahi Elementary School when there is a problem with a child, all teachers act as Guidance and Counseling teachers. This is also a special note for the government to be able to implement Guidance and Counseling teachers for elementary schools because the reason is that skilled resources start from the basics.